2013
DOI: 10.12659/msmbr.883828
|View full text |Cite
|
Sign up to set email alerts
|

Salutary effect of gastric pentadecapeptide BPC 157 in two different stress urinary incontinence models in female rats

Abstract: BackgroundSince an originally anti-ulcer stable gastric pentadecapeptide BPC 157 (PL 14736) was shown to promote healing of injured striated muscle and smooth muscle in the gastrointestinal tract, we explored its therapeutic potentials for leak point pressure (LPP) recovery in rat stress urinary incontinence (SUI) after transabdominal urethrolysis (TU) and prolonged vaginal dilatation (VD).Material/MethodsDuring a 7-day period, TU-rats and VD-rats (or healthy rats) received BPC 157, either (i) intraperitoneall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Previously, we demonstrated that BPC 157 maintains sphincter function (lower esophageal, pyloric[17,18,20-23], urethral[24], and pupil[25]). Specifically, simultaneous lower esophageal and pyloric sphincter function assessment, as a hallmark of reinstated function and tissue integrity[17,18,20-23], demonstrates that when there are more lesions present, the sphincter pressure is lower[17,18,20-23].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that BPC 157 maintains sphincter function (lower esophageal, pyloric[17,18,20-23], urethral[24], and pupil[25]). Specifically, simultaneous lower esophageal and pyloric sphincter function assessment, as a hallmark of reinstated function and tissue integrity[17,18,20-23], demonstrates that when there are more lesions present, the sphincter pressure is lower[17,18,20-23].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a similar protocol was successful in the therapy of the other fistulas, that is, gastrocutaneous ( Skorjanec et al, 2009 ), esophagocutaneous ( Cesarec et al, 2013 ), duodenocutaneous ( Skorjanec et al, 2015 ), vesicovaginal ( Grgic et al, 2016 ), and rectovaginal ( Baric et al, 2016 ) in rats. Noteworthy, as shown in separate studies, BPC 157 counteracts the known lesions in the skin ( Seiwerth et al, 1997 ; Mikus et al, 2001 ; Sikiric et al, 2003 ; Xue et al, 2004a ; Bilic et al, 2005 ; Seveljevic-Jaran et al, 2006 ; Tkalcevic et al, 2007 ; Huang et al, 2015 ), stomach ( Sikiric et al, 1997a ; Petek et al, 1999 ; Mikus et al, 2001 ; Xue et al, 2004b ; Becejac et al, 2018 ; Ilic et al, 2009 ; Ilic et al, 2011a ), duodenum ( Sikiric et al, 1994 ; Sikiric et al, 1997b ; Sikiric et al, 2001 ; Bedekovic et al, 2003 ; Amic et al, 2018 ), esophagus ( Sikiric et al, 1999b ; Petrovic et al, 2006 ; Dobric et al, 2007 ; Djakovic et al, 2016 ), colon ( Sikiric et al, 2001 ; Klicek et al, 2013 ), rectum ( Sikiric et al, 2001 ; Klicek et al, 2013 ), bladder ( Sucic et al, 2019 ), and vagina ( Jandric et al, 2013 ), whereas the fistula studies show an additional combining healing effect, providing different combinations of the lesions that were simultaneously included ( Figures 3 , 4 ), thereby a proof of the concept for a quite general healing effect ( Klicek et al, 2008 ; Skorjanec et al, 2009 ; Cesarec et al, 2013 ; Skorjanec et al, 2015 ; Baric et al, 2016 ; Grgic et al, 2016 ; Sikiric et al, 2020a ). A particular relationship was established with the NO-system, and the advantage of the BPC 157 over the corresponding standard agents (i.e., corticosteroids, sulfasalazine, H2 blockers, anticholinergics, and proton pump inhibitors) which showed only weak, if any, effect on these fistulas closing (…”
Section: Background or Overviewmentioning
confidence: 99%
“…In relation to the improved sphincter function and smooth muscle function, BPC 157 may additionally rescue the function of other failed sphincters as well [66]. This BPC 157 effect may lead to strands of newly formed muscle after intestinal anastomosis, increased anastomotic strength (and thereby, improved ileo-ileal anastomosis healing) [37,39,61] and a particular increase of muscle thickness (inner (circular) muscular layer) (more than villus height and crypt depth increased) after massive intestine resection [39].…”
Section: Mechanism Implicationsmentioning
confidence: 99%